Complex links between the energy trilemma dimensions in top 25 energy trilemma performers: The role of the UN plan of action for 2030 - Masoud Shirazi (Energy Strategy Reviews)
Humanizing energy, i.e., engaging people and communities with the energy systems, is imperative to consider the societies’ diverse perspectives, needs, and global impacts, which is essential for a balanced growth of energy trilemma (ET). Particularly, the humanizing energy may affect the complex links, e.g., synergy and trade-off, between the ET dimensions, e.g., energy equity, energy security, and environmental sustainability, influencing the policy pathfinding for balanced growth of ET. In this respect, the United Nations plan of action for 2030 especially goal seven, i.e., affordable and clean energy, associates with this purpose. Accordingly, this study addresses the dynamic multi-dimensional assessments to indicate how such agreement affects the complex links between the ET dimensions in the top 25 ET-performing countries, which are also recognized as leaders across the energy transition index. To do this, three analytical methods, e.g., the Markov switching regimes, spillover effects, and advanced sustainability analysis, are applied. The results show that complex links between the ET dimensions are time-varying and asymmetric pre- and post-the 2030 Agenda. Specifically, the Markov regime-switching analysis reveals that a dynamic combination of synergies and trade-offs can lead to a balanced growth of ET in response to the 2030 commitments under different regimes. Then, the spillover effects exhibit that the intensity and mode of synergy/trade-off throughout the short-term fluctuations of ET networks are affected by the 2030 commitments, which require supervising risk transmission management and regulations towards a balanced growth of ET. Last, the advanced sustainability analysis discloses causality between the ET dimensions through synergy, trade-off, or D-linking by different countries in response to the 2030 commitments. Consequently, combining these three applied methods serves actionable policy implications that can be instrumental in formulating strategies of humanizing energy towards a balanced growth of ET in top energy trilemma performers and potentially other analogous settings globally. These strategies should focus on connections between the “5 Ds”, e.g., decarbonization, digitalization, decentralization, disruption, and diversification, which navigate the uncertainties and complexities energy leaders face.